Determinan Pengungkapan Laporan Keuangan pada Kementerian/Lembaga - Teriyani Teriyani; Novita Weningtyas Respati; Fatimah Fatimah (Global Financial Accounting Journal, 2022)
Purpose - This study aims to test and analyze whether a total asset of, the number of work, an audit opinion, audit findings and the follow-up to the results of tests has had a significant effect on the level of the disclosure of the financial report of the ministries /state institutions. Research Method - This research uses data from ministries / institutions that have been audited by BPK during the 2016-2018 period and the 2016-2018 BPK Audit Result Summary. The population used in this study was 86 ministries / institutions throughout Indonesia with purposive sampling technique of selecting samples of 72 ministries / institutions. The analytical method used is multiple linear regression analysis. Findings - The results show that total assets and audit opinion have a positive effect on financial statement disclosure. The number of work units and the number of audit findings have no effect on the disclosure of financial statements. Meanwhile, the follow-up on examination results has a negative effect on financial statement disclosure reference and abbreviation. Implication - Hance, ministries / institutions are expected to improve human resources, especially financial report preparers to increase understanding in the field of accounting through the implementation of training in order to be able to prepare reliable and quality financial reports that can increase public accountability and transparency through a full disclosure of financial statements.